Tenth Review of IMF Data Standards Initiatives. (Policy Papers; Policy Paper, 2022)
The IMF Data Standards Initiatives enhance data transparency as a global public good. The Tenth Review updates the framework, in light of new data priorities, through a parsimonious and principles-based expansion of encouraged data categories covering selected aspects in the areas of public debt, macro-financial indicators, foreign exchange intervention, climate change-related policy, and gender- disaggregated labor market statistics. The Review also focuses on strengthening the monitoring of the first tier of the Data Standards Initiatives, the enhanced General Data Dissemination System (e-GDDS), and encouraging subscribers of the second tier, the Special Data Dissemination Standard (SDDS), to modernize data publication technology.